Drying Behavior of Khao Dawk Mali 105 Jasmine Paddy in a Spouted Bed Dryer Assisted by Microwave - Yabsungnoen, Thamarat; Treeamnuk, Krawee; Treeamnuk, Tawarat; Garluna, Jirawat (Srinakharinwirot University Engineering Journal, 2025)
This study aimed to compare the drying behavior of paddy rice using two main drying approaches: hot air drying alone and microwave-assisted drying combined with ambient air. The experiments were conducted under four drying conditions: (1) hot air drying at 80°C, (2) hot air drying at 80°C combined with microwave energy at 160 W, (3) microwave drying at 160 W combined with ambient air, and (4) microwave drying at 320 W combined with ambient air. The results showed that drying with hot air combined with microwave energy at 160 W yielded the lowest equilibrium moisture content, at 4.5% wet basis, and the highest drying rate, at approximately 1.25 gH20/min. In contrast, drying with microwave energy at 160 W combined with ambient air resulted in the highest equilibrium moisture content, at 12.5% wet basis, and the lowest drying rate, approximately 0.525 gH20/min. Furthermore, it was found that the specific energy consumption (SEC) of the hot air–microwave method tended to increase significantly in the low-moisture content region. This method also resulted in the lowest head rice yield, at 2%. On the other hand, microwave drying at 160 W alone yielded the highest head rice percentage, at 38%, and the lowest SEC. These differences indicate that excessive energy input may generate internal stresses within the kernels, leading to greater damage. Overall, the combination of hot air and microwave drying effectively reduces drying time; however, energy input must be carefully controlled to preserve the quality of the rice, particularly the head rice yield and whiteness, which may deteriorate under overly intense drying conditions.